2013
DOI: 10.1590/s0102-695x2012005000145
|View full text |Cite
|
Sign up to set email alerts
|

Study of dissolution profiles and desintegration of capsules containing the dried hydroethanolic extract of Calophyllum brasiliense

Abstract: Calophyllum brasiliense Cambess, Calophyllaceae, is of great interest in folk medicine and is used in the treatment of various diseases such as diabetes. Granules containing the hydroethanolic extract from the stem bark of C. brasiliense were obtained. The polyphenol content was standardized, and the average weight, disintegration, and the dissolution profiles of the capsules were determined after encapsulation. The capsules had an average weight of 574.5±8.0 mg. In vitro tests showed that the most efficient d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…Trata-se de planta com alto potencial madeireiro e com boa possibilidade de cultivo, especialmente em áreas úmidas, com moderado excesso de água, próximas a cursos de água (Oliveira & Joly, 2010;Schultz, 2011). A espécie também tem importância farmacêutica, por possibilitar a extração de metabólitos derivados de xantonas, cumarinas, flavonoides e terpenos, que têm ação antibacteriana, moluscicida, anti-hipertensiva e atividade contra imunodeficiência humana (HIV-1) (Noldin et al, 2006;Braga et al, 2007;Bernabé-Antonio et al, 2010;Carvalho et al, 2013).…”
Section: Introductionunclassified
“…Trata-se de planta com alto potencial madeireiro e com boa possibilidade de cultivo, especialmente em áreas úmidas, com moderado excesso de água, próximas a cursos de água (Oliveira & Joly, 2010;Schultz, 2011). A espécie também tem importância farmacêutica, por possibilitar a extração de metabólitos derivados de xantonas, cumarinas, flavonoides e terpenos, que têm ação antibacteriana, moluscicida, anti-hipertensiva e atividade contra imunodeficiência humana (HIV-1) (Noldin et al, 2006;Braga et al, 2007;Bernabé-Antonio et al, 2010;Carvalho et al, 2013).…”
Section: Introductionunclassified
“…In a study conducted by Carvalho et al (2013), the Cb extract showed high levels of polyphenolic compounds, and these natural antioxidants have great potential for the treatment of DM, as several studies have proven the hypoglycemic activity attributed to these compounds (Hou et al, 2007;Jia et al, 2009;Panda and Kar, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…5 mL of this solution were transferred to a 50 mL volumetric flask, and then 2 mL of acid phosphomolybdotungstic reagent (Sigma Co., São Paulo, Brazil) were added and the volume was completed with sodium carbonate solution of 15% (Sigma Co., São Paulo, Brazil). Later, the absorbance was measured in a 760 nm UV-VIS spectrophotometer (Shimadzu, UVmini-1240 model), according to the methodology described by Carvalho et al (2013) For the HPLC chromatographic analysis, 10 mg of CBE were weighed and added to 10 mL of methanol:water solution (2:8 v/v); then, filtered through membrane filter with a pore size of 0.45 micrometers (Millepore ® ) and analyzed by high-performance-HPLC (Shimadzu Corporation) equipped with auto injector, diode array detector scanned from 190 to 500 nm. Chromatographic conditions were: Chromatograms obtained at 350 nm, oven with temperature kept at 30°C, reverse phase column (C18), Shim-pack VP-ODS (150 × 4.6 mm; 5 µm), injection volume of 10 µL using methanol as phase A: water acidified with 0.05% of acetic acid (70:30) and acetonitrile as phase B, in proportions isocratic system of 70% phase A with flow rate of 1 mL/min.…”
Section: Quantitativementioning
confidence: 99%
See 1 more Smart Citation
“…It features a wide variety of secondary metabolites isolated from leaves, bark, roots, flowers and fruits, such as xanthones, terpenes, chromanones and flavonoids, which exhibit multiple medicinal properties (Noldin et al, 2006;Bernabé-Antônio et al, 2010;Carvalho et al, 2013). It is also suitable for reforestation, especially to restore the vegetation in locations subjected to periodic short-term floods, as well as areas with a permanently soggy soil (Carvalho, 1994;Souza, 2009).…”
Section: Introductionmentioning
confidence: 99%